(untitled) (Al-Qamar, 2021)
An orientalist is a non-Muslim who is an expert in oriental studies. Orientalism is the study of Eastern values, Culture, Art, and the Religion of Islam by a non-Muslim of the West. Most orientalists criticized Islam. Karen Armstrong is also an orientalist but author tried to show the real image of Islam in the west. Her book “Muhammad: A Prophet of our Time” is an analytical study of the biography of Holy Prophet SAW. She made five chapters named: 1. Mecca, 2. Jahilliyah, 3. Hijrah, 4. Jihad, and 5. Salam. She tried to make a positive analysis but sometimes she misunderstood some situations. She also advised other orientalists to be moderate. In the last, she explained some Islamic terminologies and also add images of the cities discussed in the book. So, I analyzed her book and also tried to explain her misunderstandings.